2022
DOI: 10.3390/gels9010005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Branched Alkyl Chain Length on the Properties of Supramolecular Organogels from Mono-N-Alkylated Primary Oxalamides

Abstract: Mono-N-alkylated primary oxalamide derivatives with different sized branched alkyl tail-groups were excellent low molecular weight gelators for a variety of different organic solvents with different polarities and hydrogen-bonding abilities. Solvent-gelator interactions were analyzed using Hansen solubility parameters, while 1H NMR and FTIR spectroscopy were used to probe the driving forces for the supramolecular gelation. The molecular structures of the twin tail-groups did not significantly affect the supram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Although individual fibers are difficult to discern within bundles and in densely entangled regions at the magnifications shown in Figure , the fibers are estimated to have widths in the 0.1–1 μm range and lengths in the 100–1000 μm range. These results indicate that the compound AOx24 undergoes hierarchical self-assembly to form fibrous structures that entangle to form 3D SAFINs, which leads to the formation of stable organogels (Figure ) through the entrapment of the SO, Cin, and Tw80 solvent molecules as well as BCl and trace water molecules, which is also consistent with the self-assembly of AOx24 and other N -alkylated primary oxalamides in other organic solvents. , Note that the corresponding xerogels were not examined at higher magnification by SEM because SO, Cin, and Tw80 are all nonvolatile and hindered sample preparations. These results confirm that AOx24 should be able to form networks of submicron-scale fibers within the dispersed oil droplets, which should provide surfaces for BCl to adsorb to via weak, noncovalent interactions and/or provide a tortuous path to hinder diffusion within and egress from the oil phase.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Although individual fibers are difficult to discern within bundles and in densely entangled regions at the magnifications shown in Figure , the fibers are estimated to have widths in the 0.1–1 μm range and lengths in the 100–1000 μm range. These results indicate that the compound AOx24 undergoes hierarchical self-assembly to form fibrous structures that entangle to form 3D SAFINs, which leads to the formation of stable organogels (Figure ) through the entrapment of the SO, Cin, and Tw80 solvent molecules as well as BCl and trace water molecules, which is also consistent with the self-assembly of AOx24 and other N -alkylated primary oxalamides in other organic solvents. , Note that the corresponding xerogels were not examined at higher magnification by SEM because SO, Cin, and Tw80 are all nonvolatile and hindered sample preparations. These results confirm that AOx24 should be able to form networks of submicron-scale fibers within the dispersed oil droplets, which should provide surfaces for BCl to adsorb to via weak, noncovalent interactions and/or provide a tortuous path to hinder diffusion within and egress from the oil phase.…”
Section: Resultssupporting
confidence: 57%
“…Especially Tw80, CA, and water, which possess both hydrogen bond accepting and donating groups, could disrupt the intermolecular hydrogen bonding of AOx24 molecules. Interestingly, AOx24 formed a gel with Tw80 (Figure f) at 2 wt %, which is not all that surprising since the structure of Tw80 has three oxyethylene groups and considering that AOx24 is also a good gelator for the oxyethylene solvents ethylene and propylene glycol . Gelation tests carried out in the presence of BCl in both SO and Cin confirmed that BCl does not significantly disrupt the gel networks formed by AOx24 (Figure b,e).…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations